I was here - Forman, Gayle (New York : Viking, published by the Penguin Group, 2015)
In an attempt to understand why her best friend committed suicide, eighteen-year-old Cody Reynolds retraces her dead friend's footsteps and makes some startling discoveries.
Keywords: Suicide -- Fiction; Grief -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Mystery and detective stories; Washington (State) -- Fiction